O God of players : the story of the Immaculata Mighty Macs - Byrne, Julie, 1968- (Religion and American culture (New York, N.Y.), 2003)
Between 1972 and 1974, the Mighty Macs of Immaculata College -- a small Catholic women's school outside Philadelphia -- made history by winning the first three women's national college basketball championships ever played. A true Cinderella team, this.